THE INFLUENCE OF PRODUCT QUALITY AND DIRECT ENGAGEMENT ON INTEREST TO BUY BACK WITH TRUST INTERVENING VARIABLES - Nanda Anggi Putrisia; Dwi Suryanto Hidayat (Jurnal Ekonomi, 2022)
This study aims to determine the effect of product quality and involvement on repurchase interest in a case study of Micro, Small and Medium Enterprises (MSMEs) of Lasem batik. The data used in this study is primary data based on a sample of 120 respondents. The data is processed using a smart PLS or Smart Partial Least Square system. The analysis technique in this study consists of two sub-models, namely the measurement model or the outer model and the structural model or the inner model. The data was collected using a questionnaire to the respondents. The data analysis technique used multiple linear regression analysis techniques. The results of the analysis prove that product quality has an effect on repurchase interest. Involvement has no effect on repurchase interest. Then trust has an effect on repurchase interest